The administration of anthelmintics by intraruminal injection in cattle - Pinheiro, Alfredo C.; Echevarria, Flávio A. (Pesquisa Agropecuaria Brasileira, 2014)
The application of anthelmintics by intraruminal inoculation proved to be a practical method in cattle. Intraruminal application was 70 to 80% more active than that one given orally. No adverse effect was observed from the intraruminal injection of Rafoxanide, Parbendazole, and Morantel, in 1,000 animals which included calves, dry cows and milking cows.